Activity-based hospital payments: a qualitative evaluation by Israeli managers and physicians. (13th November 2019) - Waitzberg, R; Quentin, W; Busse, R; Greenberg, D
Abstract: Background: Israel has expanded procedure-related group (PRG) payments instead of per-diem payments for hospitals. There is scarce literature that documents the process of adoption of DRGs and its entailed economic incentives according to hospital workers' perspectives. Important issues remain underexplored such as how managers transmit the incentives and considerations to caregivers, how physicians embrace (or not) these new rules of the game. Methods: We used qualitative, grounded-theory analysis based on 35 semi-structured in-depth interviews with managers, financial directors, surgical ward heads and physicians in 5 hospitals, sampled by maximum variation according to hospital characteristics. Results: We found two main themes: incentives for change and barriers to change. The most significant change was the creation of a common professional language, which facilitates measurement and supervision of activities, outcomes, and profitability. Measurement enhances transparency and is essential for resource management. Respondents also reported barriers inhibiting their responsiveness to the economic incentives of PRGs: a complicated coding system; inappropriate pricing; dependency on numerous production factors; lack of transparency; lack of coordinated goals among players; and other medical or moral considerations that outweigh or co-exist with financial considerations. Conclusions: The adoption of PRGs led to changes in managers' and physicians' actions and considerations, particularly in situations where it was possible to reprioritize elective procedures without harming patient health or quality of care. However, on a broader level, the impact was modest, leading mainly to a fairer redistribution of resources and the rearrangement of work, such as shifting patients to after-hours. It would be appropriate to allow hospitals and physicians to operate in a less restricted market where regulation allows suppliers some degree of discretion so they can react to the PRG reform. Key messages: Provider payment reforms change economic incentives, behavior and decision-making. However, structural barriers and other non-economic considerations may lead to unintended consequences of such reforms.